Design of interdigital bandpass filter / Kamarul Hasrin Omer - Omer, Kamarul Hasrin (2004)
The purpose of this project is to design, fabricate and measure the characteristics of a microstrip interdigital bandpass filter operating at microwave frequencies using computer-aided design package. The filter was designed using conventional circuit simulator and electromagnetic circuit simulator such as HP Eesoft Libra and GENESYS Eagleware. Before this, other types of filters with different topologies have already been designed by other students such as bandpass filter, Chebyshev, Butterworth low-pass and parallel coupled bandpass filter. The filter specification calls for a 0.5 dB passband ripple at a center frequency of 5 GHz with a bandwidth of 8%. The filter has an insertion loss not exceeding 6 dB in the passband and more than 20 dB in the stopband. Rogers RT/Duroid microstrip laminates microstrip with a 0.5 mm substrate thickness and a relative permittivity of 2.33 were used to build the filter. Measurements were carried out using a vector network analyzer at the Microwave Technology Center. The filter was synthesized based on the above specification. Results from simulation were compared with the measurements from vector network analyzer to determine the successflilness of the design.